Interpretation Of Social Professions In “Mahbub Ul-Kulub” By Alisher Navoi (Eurasian Journal of Learning and Academic Teaching, 2023)
This article discusses the social professions expressed in the work "Mahbub ul-Kulub". Their role in society was widely discussed.